Adult congenital heart disease nurse coordination: Essential skills and role in optimizing team-based care a position statement from the International Society for Adult Congenital Heart Disease (ISACHD). (15th February 2017) - Sillman, Christina; Morin, Joanne; Thomet, Corina; Barber, Deena; Mizuno, Yoshiko; Yang, Hsiao-Ling; Malpas, Theresa; Flocco, Serena Francesca; Finlay, Clare; Chen, Chi-Wen; Balon, Yvonne; Fernandes, Susan M
Abstract: Background: Founded in 1992, the International Society for Adult Congenital Heart Disease (ISACHD) is the leading global organization of professionals dedicated to pursuing excellence in the care of adults with congenital heart disease (CHD) worldwide. Among ISACHD's objectives is to "promote a holistic team-based approach to the care of the adult with CHD that is comprehensive, patient-centered, and interdisciplinary" (http://www.isachd.org ). This emphasis on team-based care reflects the fact that adults with CHD constitute a heterogeneous population with a wide spectrum of disease complexity, frequent association with other organ involvement, and varied co-morbidities and psychosocial issues. Methods: Recognizing the vital role of the adult CHD (ACHD) nurse coordinator (ACHD-NC) in optimizing team-based care, ISACHD established a task force to elucidate and provide guidance on the roles and responsibilities of the ACHD-NC. Acknowledging that nursing roles can vary widely from region to region based on factors such as credentials, scopes of practice, regulations, and local culture and tradition, an international panel was assembled with experts from North America, Europe, East Asia, and Oceania. The writing committee was tasked with reviewing key aspects of the ACHD-NC's role in team-based ACHD care. Results/conclusion: The resulting ISACHD position statement addresses the ACHD-NC's role and skills required in organizing, coordinating, and facilitating the care of adults with CHD, holistic assessment of the ACHD patient, patient education and counseling, and support for self-care management and self-advocacy.